catena-Poly[[[2-(1,3-thiazol-4-yl)-1H-benzimidazole]manganese(II)]-μ-oxalato] - Peng Liang; Li-Ning Huang; Xian-Hong Yin (Acta Crystallographica Section E, 2013)
In the title compound, [Mn(C2O4)(C10H7N3S)]n, the MnII cation is chelated by one 2-(1,3-thiazol-4-yl)-1H-benzimidazole ligand and two oxalate anions in a distorted N2O4 octahedral geometry. Two independent oxalate anions are located on individual inversion centers and bridge the MnII cations into a polymeric chain running along [101]. The thiazole ring is approximately coplanar with the benzimidazole ring system [dihedral angle = 4.19 (9)°]. In the crystal, classical N—H...O hydrogen bonds and weak C—H...O hydrogen bonds link the polymeric chains into a three-dimensional supramolecular architecture.